2019
DOI: 10.1002/cche.10141
|View full text |Cite
|
Sign up to set email alerts
|

Optimized qualitative and quantitative methods for barley viability testing using triphenyl tetrazolium chloride staining

Abstract: Background and objectives Barley viability is an important agronomic trait and has a direct influence on subsequent beer production. Traditional triphenyl tetrazolium chloride (TTC) test evaluating seed viability still has some drawbacks, for example, excessive instability and time consumption. In the present study, we optimized both the qualitative and quantitative TTC seed viability test methods, and established more accurate and convenient assays to evaluate barley seed viability. Findings In the qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…quadrangulosa although all three species had similar TZ viability scores. In contrast, Ma et al (2019) observed a positive correlation between TZ viabilities and vigour however they were studying different batches of a single species. The TZ seed vigour test is not an effective measure of vigour when comparing different species, especially where there are significant differences in seed size, as with the 15 species of eucalypts studied here.…”
Section: Correlations Between Tz Seed Viability Vigour and Seed Massmentioning
confidence: 87%
“…quadrangulosa although all three species had similar TZ viability scores. In contrast, Ma et al (2019) observed a positive correlation between TZ viabilities and vigour however they were studying different batches of a single species. The TZ seed vigour test is not an effective measure of vigour when comparing different species, especially where there are significant differences in seed size, as with the 15 species of eucalypts studied here.…”
Section: Correlations Between Tz Seed Viability Vigour and Seed Massmentioning
confidence: 87%
“…After 2 days, when the seeds were just budding, seeds were collected and homogenized in water to produce crude enzyme extract. The seed viability was assessed using quantitative 2,3,5-triphenyltetrazolium chloride (TTC) assay [21]. The content of triphenyl tetrazolium formazan (TTF) produced by dehydrogenase per gram of seed in 1 h was used as seed vigor index.…”
Section: Effect Of Soaking Seeds With Ice6 On Seed Vigor During Germi...mentioning
confidence: 99%
“…Seed vigor is an important comprehensive index to reflect the quality of seeds, and it is a characteristic of high germination rate [24]. The TTF content in seeds is positively correlated to germination rate [21], which was used as the seed vigor index. In the…”
Section: The Seed Vigor Was Improved By Soaking With Ice6mentioning
confidence: 99%
See 2 more Smart Citations